Exploring Budget Performance and Budget Implementation Research From 2006–2025: A Prisma-Based Bibliometric Analysis - Pratiwi, Luh Winda; Purbawangsa, Ida Bagus Anom; Sri Artini, Luh Gede; Rahyuda, Henny (AIBPM Publisher, 2025)
Delays in budget realization represent a critical challenge in public sector financial management, as they undermine the efficiency and effectiveness of government program implementation. This study aims to identify publication trends in the budget performance and budget implementation literature over a two-decade period. The study uses a combination of bibliometrics using VOSviewer and the PRISMA method to obtain appropriate articles. Forty-nine articles were analyzed in the initial stage based on the Lens.org database. After going through a selection process based on exclusion and inclusion criteria, 18 articles were obtained, which were extracted in depth for thematic synthesis. Bibliometrics show the dominance of budget performance and implementation themes, with the latest trend towards evaluation and transparency. Topics such as efficiency and performance evaluation are still rarely studied and can potentially become the focus of further research. This study is one of the first bibliometric analyses to explore the relationship between budget implementation and budget performance using the PRISMA approach and bibliometrics via VOSviewer in the past 20 years